O artigo de opinião no ensino fundamental: articulações didáticas entre leitura e escrita em atividades orientadas pelos estudos da argumentação e da semiótica - Costa, Maria da Luz da Silva (Universidade Federal do Tocantins, 2021)
This research deals with the teaching of the opinion article genre in the 9th grade of Elementary School and proposes the presentation of practices that articulate reading and writing, considering their inseparability for the development of argumentative competence. As a general objective, it aims to develop the competence of students to produce texts of this kind, well articulated from a formal point of view, coherent and persuasive from an argumentative point of view, at the same time taking into account a position that is committed to a more humanitarian dimension of society. Based on studies on argumentation developed since Classic Rhetoric, we consider its contribution to the understanding of strategies mobilized by the speaker (enunciator) with a view to the adhesion of the audience (enunciate), in different genres, but, more emphatically, in the genre article of opinion. As our demand as ProfLetras researchers aims to define, from the theoretical field, the field of application, thinking of didactic strategies that contribute to the quality of pedagogical practices, we developed a set of workshops, organized around current themes that discuss different issues , also considering the way in which contemporary themes and reading and writing practices are oriented since the BNCC - Common National Curriculum Base (BRASIL, 2018). The research follows a qualitative approach, guided by discourse studies, more specifically arising from discursive semiotics and rhetoric, theorizations from which we elaborate a pedagogical proposal to develop the competence for a critical reading of opinion articles, favoring the apprehension of different argumentative strategies and, from then on, subsidize the practice of textual production. As a final product, we bring a notebook that systematizes the proposals for the workshops, explaining the activities related to them and justifying their way of constitution and sequence.